Effective Police Station Legal Advice - Country Report 3: Ireland - Kemp, Vicky (University of Nottingham, 2018)
This Country Report for Ireland has arisen out of a comparative study into police station legal advice, led by Dr Vicky Kemp, University of Nottingham. She received a small grant from the British Academy/Leverhulme to undertake semi-structured interviews with defence lawyers and policy officers responsible for criminal legal aid in six jurisdictions.